THE THEORY OF AGGLUTINATION AND THE PROBLEMS OF STUDYING THE MORPHEMICS OF TURKIC LANGUAGES - Kuchimova, Gulmera (Журнал иностранных языков и лингвистики, 2023)
The theory of agglutination is actually one of the hypotheses of the origin of inflectional forms in the Indo-European languages, according to which the person-numbers and possessive forms of the verb are formed from independent pronouns, and they are attached to the stem, and the suffix (affix, suffix) grew from the primary aspect turning into morphemes. The complete formation of the comparative historical method in Western linguistics, which forms the basis of the theory of agglutination, dates back to the first quarter of the 19th century. During this period, the works of Franz Bopp (1791-1867), Rasmus Rask (1787-1832) and Jacob Grimm (1785-1863), leading representatives of comparative studies, were published, which laid the foundation for the further development of language science. the science. Although the theory of agglutination is a product of Indo-European linguistics, when it became clear that true agglutination is a characteristic of the languages belonging to the Altaic language family, including the Turkic languages, the theory of agglutination was mainly based on the morphology and morphemics of the Turkic languages and became the theoretical and methodological basis of research by morphemic.